BIODIVERSITY OF ZOOBENTHOS AT THE CA RIVER, VIETNAM - Huy, Chien Nguyen (Research Center for Oceanography - Indonesian Institute of Sciences (LIPI), 2008)
A research on zoobenthos biodiversity was carried out from September 2004 to September 2006 at the Ca river (the length of Nghe An and Ha Tinh provinces) showed a species composition consisted of 154 species, 115 genera, 72 families, 32 orders and 5 phyla, including Mollusca, Annelida, Arthropoda, Echinodermata and Sipuncula. The results showed that a decreasing trend in the number of zoobenthos species from the fresh water area to the estuary of the Ca River. The largest number of species was shown in route 1 (Cua Hoi) with 89 species (nearly 44.7%). The lowest value of species number was seen at route 5 with 31 species (15.5%). The Crustacea group was the most predominant group, including 47 species. The H' and d indexes indicated a decreasing biodiversity level from route 5 (Hung Lam, H' = 0.9 and d = 0.75) to route 1 (Cua Hoi, H' = 2.32 and d = 1.96). The average number of zoobenthos density was 149 individuals per m2. The average value in dry season was higher than that in rainy season (151 individuals per m2 compared to 146 individuals per m2, respectively). In the dry season, the biological indexes changed mainly according to salinity and turbidity factors. Meanwhile, in rainy season, the variation of zoobenthos species related essentially to other factors, DO and salinity.